Brain structure in children with congenital visual disorders and visual impairment. (8th August 2019) - Bathelt, Joe; Dale, Naomi J; de Haan, Michelle; Clark, Chris A
Abstract : Aim: To examine if congenital visual impairment is associated with differences in brain anatomy in children. Method: Ten children (8–12y) with congenital disorders of the peripheral visual system with severe visual impairment (SVI; >0.8 logMAR) or mild‐to‐moderate visual impairment (MVI; 0.6–0.8 logMAR) were compared to 21 typically sighted comparison (TSC) children. Thalamus volume, grey matter density, white matter microstructure, and integrity of visual tracts were investigated in SVI, MVI, and TSC groups with anatomical and diffusion‐weighted magnetic resonance imaging. Results: Compared to the TSC group, the SVI group had lower white matter integrity in tracts of the visual system (optic radiations: SVI 0.35±0.015, TSC 0.39±0.007 [ p =0.022]; posterior corpus callosum: SVI 0.37±0.019; TSC 0.42±0.009 [ p =0.033]) and lower left thalamus volume (SVI 4.37±0.087; TSC 4.99±0.339 [ p =0.015]). Neuroanatomical differences were greater in the SVI group, while no consistent differences between the MVI and TSC group were observed. Interpretation: Posterior tracts of the visual system are compromised in children with congenital visual impairment versus those who are typically sighted. The severity of visual input appears to have affected neuroanatomical development as significant reductions were only found in the SVI group. What this paper adds: Severe visual impairment in mid‐childhood is associated with reduced integrity of visual pathways and reduced thalamus volume. What this paper adds: Severe visual impairment in mid‐childhood is associated with reduced integrity of visual pathways and reduced thalamus volume. This article is commented on by Bauer on page 16 of this issue.